PENGEMBANGAN MEDIA WORDLY CARDS BERBASIS AUGMENTED REALITY (AR) MELALUI APLIKASI ASSEMBLR EDU PADA MATERI KOSAKATA KELAS IV DI SDN - Umar, Nurfatima; Husain, Rusmin; Pulukadang, Wiwy T.; Halidu, Salma; Katili, Sukri (EDUTECH : Jurnal Inovasi Pendidikan Berbantuan Teknologi, 2025)
Digital-based learning technology is rapidly advancing, one of which is the application of Augmented Reality (AR) in educational media.  The purpose of this research is to develop Wordly Cards Based on Augmented Reality (AR) as a learning media, which are AR-based vocabulary cards designed using the Assemblr Edu application, making them suitable for use in Indonesian language learning on the topic of Loanwords. The research method used is the Research and Development method, employing the ADDIE development model, which includes Analysis, Design, Development, Implementation, and Evaluation. The analysis stage is conducted to understand user needs, followed by the design and development of cards containing AR content using the Assemblr Edu application.  Implementation was carried out with a trial of the developed product.  Evaluation is conducted by dividing pre-test and post-test questions to measure the effectiveness of the media. Media Wordly Cards Based on Augmented Reality (AR) as a learning medium for fourth-grade students at SDN 8 Kabila, is declared very suitable for use as a teaching medium.  Based on the results of media expert validation, it received a percentage of 100% with the category "Very Feasible," material expert validation received a percentage of 90.7% with the category "Very Feasible," and language expert validation received a percentage of 95.8% with the category "Very Feasible."  The assessment by the fourth-grade homeroom teacher as a user expert of the developed Wordly Cards Based on Augmented Reality (AR) media received a percentage of 98.2% with the category "Very Feasible."  The recapitulation of the expert validation results obtained a percentage of 96.1%, thus the Wordly Cards Media Based on Augmented Reality (AR) is declared very feasible to use. ABSTRAK Teknologi pembelajaran berbasis digital semakin berkembang pesat, salah satunya melalui penerapan Augmented Reality (AR) dalam media edukasi. Tujuan penelitian ini adalah mengembangkan media pembelajaran Wordly Cards Berbasis Augmented Reality (AR) yaitu kartu kosakata berbasis AR yang dirancang menggunakan aplikasi Assemblr Edu sehingga layak untuk digunakan pada pembelajaran Bahasa Indonesia materi Kosakata Serapan. Adapun metode penelitian yang digunakan adalah metode penelitian pengembangan (Research and   Development) dengan menggunakan model penelitian pengembangan ADDIE yaitu Analysis, Design, Development, Implementation, dan Evaluation. Tahap analisis dilakukan untuk memahami kebutuhan pengguna, diikuti dengan perancangan dan pengembangan kartu yang memuat konten AR menggunakan aplikasi Assemblr Edu. Implementasi dilakukan dengan uji coba produk yang dikembangkan. Evaluasi dilakukan dengan membagi soal pre test dan post test untuk mengukur keefektifan media. Media Wordly Cards Berbasis Augmented Reality (AR) sebagai media pembelajaran untuk peserta didik kelas IV SDN 8 Kabila, dinyatakan sangat layak digunakan sebagai media ajar. Berdasarkan hasil validasi ahli media, mendapatkan presentase 100% dengan kategori “Sangat Layak”, validasi ahli materi mendapatkan presentase 90,7% dengan kategori “Sangat Layak”, validasi ahli Bahasa mendapatkan presentase 95,8% dengan kategori “Sangat Layak”. Penilaian oleh wali kelas IV sebagai ahli pengguna terhadap media Wordly Cards Berbasis Augmented Reality (AR) yang dikembangkan mendapatkan presentase 98,2% dengan kategori “Sangat Layak”. Rekapitulasi hasil validasi ahli mendapatkan persentase 96,1% sehingga Media Wordly Cards Berbasis Augmented Reality (AR) dinyatakan sangat layak digunakan.